Correlation Between Abdominal Muscle Strength and Pulmonary Function in Subjects with Low Back Pain - Pranita Bhavsar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Low back pain is a broad term encompassing pain, muscle tension, or stiffness localized below the costal margin and above the inferior gluteal folds. Reviewing of previous studies shows that low back pain is partly caused by weak abdominal muscles. Developing strong abdominal muscles may help prevent back pain by making individual less prone to back injuries. Few studies have been done to find out the relation between expiratory muscle and pulmonary function. Pulmonary function test provide the clinician with information about integrity of the airways. Pulmonary disease are classified into 3 basic categories; Obstructive, Restrictive, Combined. To diagnose the respective pulmonary condition Forced Vital Capacity (FVC), Forced Expiratory Volume in One sec. (FEV1) Peak Expiratory Flow Rate (PEFR), “Curl up” was examined. Observational study was carried out with 60 samples by using convenient sampling in the duration of 6 months at Dr.UlhasPatil College of Physiotherapy. After ethical committee consideration Subjects were enrolled according to selection criteria. With respect to the objective mentioned there is no correlation between Abdominal Muscle Strength and FEV1/FVC, as the r value is 0.04 and the P value was 0.72. It suggested that abdominal strengthening may help in good pulmonary function and may assist the ventilatory process along with maximum forceful exhalation with correct breathing techniques and posture.